(untitled) (Homoeopathy for All, 2023)
In the recent times, endocrine disorders have seen a rise in trend, of which Diabetes mellitus (DM) and Thyroid disorders are the most common ones. A patient suffering from thyroid dysfunction for a long duration may develop diabetes or vice versa. Ultimately, both of these disorders tend to co-exist in the patients suffering from one or the other for a prolonged duration. Such metabolic and endocrine related disorders tend to affect the body in multiple ways, which may clinically represent as body mass or weight changes, restriction in growth pattern, impairment in functioning of other vital organs, psychological changes and so on. These disorders may co exist maximum in adult males or females, antenatal scenario, and less commonly in adolescence. Many physicians are able to manage both the conditions independently. However, when it comes to their co-existence there are many obstacles experienced by a practitioner. This article focuses on the relationship between thyroid gland disorders and diabetes mellitus in the population and their possible homeopathic management as per the literature.